2003
DOI: 10.1046/j.1525-1403.2003.t01-1-03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Tip Granuloma Associated with Sacral Region Intrathecal Drug Administration

Abstract: Spinal cord compression from catheter tip granulomatous masses following intrathecal drug administration may produce devastating permanent neurologic deficits. Some authors have advocated intrathecal catheter placement below the conus medullaris to avoid the possibility of spinal cord involvement. Multiple cases of catheter tip granulomas in the thoracolumbar region have been reported. We present a unique case of a sacral region catheter tip inflammatory mass producing permanent neurologic deficits. A 71-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The continuous contact with the neural tissue may have caused an extraordinary local concentration of morphine, and this may have predisposed our patient to the development of the ICTG. Another report has shown that an ICTG can be formed at the sacral level . Therefore, other factors that may contribute to ICTG formation should also be sought.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous contact with the neural tissue may have caused an extraordinary local concentration of morphine, and this may have predisposed our patient to the development of the ICTG. Another report has shown that an ICTG can be formed at the sacral level . Therefore, other factors that may contribute to ICTG formation should also be sought.…”
Section: Discussionmentioning
confidence: 99%
“…We also reviewed the bibliographies of the studies identified by the electronic database search and retrieved other relevant studies. There were 27 relevant original case series and case reports identified . Two case reports of ICTG developed in patient receiving non‐opioid medications were excluded from analysis because development of ICTG in these patients remains very rare .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, ICTGs have occurred with IT infusions of morphine (74,79,86,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109) or hydromorphone (86,110). In contrast, though less widely employed for IT infusions and with one exception (111), no granulomas have been reported in patients receiving IT admixtures with fentanyl as the IT opioid.…”
Section: Etiology Of Intrathecal Granulomasmentioning
confidence: 99%
“…Furthermore, none of the 18 patients receiving bupivacaine in combination with fentanyl, in this study, developed granuloma. Indeed, ICTGs have been reported to occur with intrathecal infusions of morphine (6)(7)(8)(10)(11)(12)(13)(14)(15)18,19,22,(25)(26)(27)(31)(32)(33)(52)(53)(54)(55)(56)(57), or hydromorphone (13,23,58,59). However, the vast majority of reported hydromorphone-related ICTG cases had also been exposed to morphine prior to receiving hydromorphone, and therefore, it was not clear whether the ICTG was purely a phenomenon related to intrathecal hydromorphone infusions (13,17,18,23,33,59).…”
Section: The Role Of Intrathecal Agents Concentration and Dose In Imentioning
confidence: 99%